Computer Simulation of the Response of Amperometric Biosensors in Stirred and non Stirred Solution - Baronas, R.; Ivanauskas, F.; Kulys, J. (Nonlinear Analysis: Modelling and Control, 2003)
A mathematical model of amperometric biosensors has been developed to simulate the biosensor response in stirred as well as non stirred solution. The model involves three regions: the enzyme layer where enzyme reaction as well as mass transport by diffusion takes place, a diffusion limiting region where only the diffusion takes place, and a convective region, where the analyte concentration is maintained constant. Using computer simulation the influence of the thickness of the enzyme layer as well the diffusion one on the biosensor response was investigated. The computer simulation was carried out using the finite difference technique.
Keywords: reaction-diffusion; modelling; biosensor